Developing an Arduino Uno-Based Water Clarity Assessment Instrument at LIPI-Biotechnology - Euis Suryati; Rahmat Ramadhan; Siti Farah Fakhirah; Asa Yuaziva; Jonser Steven Rajali Manik; Icha Maulidya (Batrisya Education, 2026)
Visual monitoring of water clarity in closed laboratory reservoirs poses significant challenges and inefficiencies that may compromise equipment sterilization standards. This study aims to develop an automated water clarity monitoring system at the Research Center for Biotechnology-LIPI utilizing an Arduino Uno microcontroller paired with a BH1750 digital light sensor. The device operates on the principle of light transmission, where suspended particles in turbid water obstruct the light intensity detected by the sensor. Data is processed and transmitted via an Ethernet Shield to a web-based interface for both real-time monitoring and database logging. The research results demonstrate that the device successfully classifies water clarity levels based on light intensity readings, defining clear water as >200 Lux, moderate water as 150-200 Lux, and turbid water as <150 Lux. By providing real-time status updates and automated historical data logs, the system eliminates the need for manual physical inspection. This instrument presents a functional and cost-effective solution to ensure adherence to laboratory water quality standards.